In the Days of Noah: Urzeit/Endzeit Correspondence and the Flood Tradition in 1 Peter 3-4 - Marcar, Katherine ca. 20./21. Jh. (New Testament studies, 2017)
Much Petrine scholarship has focused on unravelling the Enochic traditions in 1 Pet 3.18-20. However, these investigations have largely overlooked the role of Noah and the flood in 1 Peter. This article seeks to rectify this deficiency by examining how Second Temple Jewish and early Christian texts used the primeval flood as a paradigm for the eschaton, a clear example of Urzeit/Endzeit correspondence. Once the Petrine use of the flood traditions is interpreted in this light, new solutions emerge not only for this difficult text, but also for the larger section of 1 Peter 3-4. Four specific points of correspondence are investigated: first, the righteousness of Noah as the righteousness of Christ (and also, believers); second, the wickedness of the flood generation as the wickedness of contemporary Gentile society; third, Noah's preaching to the flood generation as believers' witness to their countrymen; and finally, the opportunity of repentance during Noah's lifetime as a similar opportunity for mission in contemporary Asia Minor. A robust understanding of the Noah traditions paves the way for a clearer understanding of the apocalyptic character of 1 Peter and its contemporary application to the Christians of Asia Minor.